2019
DOI: 10.5114/fmpcr.2019.82982
|View full text |Cite
|
Sign up to set email alerts
|

Primary health care quality in Iran: a systematic review and meta-analysis

Abstract: A -Study Design, B -Data Collection, C -Statistical Analysis, D -Data Interpretation, E -Manuscript Preparation, F -Literature Search, G -Funds Collection Quality measurement is the first step in improving overall quality. Servqual has been identified as one of the most important methods frequently used in assessing the quality of healthcare services. This study aims to systematically review and conduct meta-analysis of conducted studies in this regard in which Servqual tools were used to assess and measure th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…In the present study, according to the SERVQUAL model, patients' expectations were higher than their perceptions in all dimensions of service quality, and evaluation of their perceptions indicated their dissatisfaction. Similar to the current study, multiple studies have reported large gaps between the expectations and perceptions of service quality in all dimensions (23)(24)(25)(26)(27)(28)(29). The largest gap was observed in the dimensions of responsiveness, empathy, and accessibility; nevertheless, the smallest gap was related to tangibility.…”
Section: Discussionsupporting
confidence: 80%
“…In the present study, according to the SERVQUAL model, patients' expectations were higher than their perceptions in all dimensions of service quality, and evaluation of their perceptions indicated their dissatisfaction. Similar to the current study, multiple studies have reported large gaps between the expectations and perceptions of service quality in all dimensions (23)(24)(25)(26)(27)(28)(29). The largest gap was observed in the dimensions of responsiveness, empathy, and accessibility; nevertheless, the smallest gap was related to tangibility.…”
Section: Discussionsupporting
confidence: 80%
“…Previous findings also corroborate that patients who are older, are married, and have a lower level of education, lower incomes, and a good health status receive a higher level of HSQ (Pekkaya, İmamoğlu, & Koca, 2017; Schoenfelder et al, 2011). However, most studies measure the HSQ based on general hospital care or the performance of the health system (Gorji et al, 2019; Nadi et al, 2016; Price et al, 2014), and only a few studies have focused on NPP. Therefore, the aims of this study were as follows: (a) to investigate the expectations, perceptions, and gaps of the HSQ, from the patients’ perspective, and (b) to explore further the priority dimensions for improvement and the significant factors associated with the HSQ in NPP.…”
mentioning
confidence: 99%
“…One systematic review revealed that the largest gap of the HSQ dimension is in responsibility, while the smallest gap is in tangibility and empathy (Teshnizi et al, 2018). However, other studies have suggested that the largest gap is in the reliability or tangibility dimension and that the smallest gap is in the responsiveness or assurance dimension (Gorji et al, 2019;Rezaei, Hajizadeh, Zandian, Fathi, & Nouri, 2018). Consequently, the gaps of HSQ are controversial, and they may vary, based on the different healthcare systems and cultures.…”
mentioning
confidence: 99%
“…The first level is related to PHC, while the second and third levels concern hospital services provided in urban areas [11]. PHC in Iran is provided through a healthcare network which was established in the mid-1980s, referred to as the first major reform in Iran's healthcare system [6]. Health houses in rural areas provide PHC through trained local residents called "Behvarz", under the supervision of rural healthcare centers.…”
Section: Primary Health Care Fps and The Referral System In Iranmentioning
confidence: 99%
“…The best approach to providing PHC is suggested to be through the use of FPP [5]. The World Health Organization (WHO) introduced the Family Physician Program (FPP) as a vital tool for improving quality, reducing costs, and ensuring effectiveness and equality [6]. Establishing an FPP within a healthcare system can support an appropriate referral system that works more efficiently and increases access to services [5,7].…”
Section: Introductionmentioning
confidence: 99%